Do not jump and start expanding the squares.
In equation (1), both the squares will yield either positive number or 0. Since sum of two positive number cannot be 0, each of the term must be 0
∴ 3x + 2y -22 = 0
Multiplying by 2, and adding both equation
6x + 4y - 44 = 0
5x - 4y = 0
=) x = 4
Putting the value of x in the equation
5 x 4 – 4y = 0
y = 5
∴ x+y = 9
Correct Answer: 9
All features of the online course, including the classes, discussion board, quizes and more, on a mobile platform.
Download videos onto your mobile so you can learn on the fly, even when the network gets choppy!